2006
DOI: 10.1111/j.1398-9995.2006.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, classification and perception of allergic and nonallergic rhinitis in Belgium

Abstract: We found a high prevalence of self-declared rhinitis symptoms in the Belgian population, AR being about three times more prevalent than NINA. In addition, AR patients suffered from a greater number of symptoms and displayed a more 'persistent' and 'moderate-severe' ARIA profile than NINA. About 75% of patients seeking medical help suffer from 'moderate to severe' forms of rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
6
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 15 publications
9
146
6
13
Order By: Relevance
“…However, in tree pollen allergy, many monosensitized subjects develop symptoms in old age (43,44). On the other hand, NAR appears to be more common in subjects over 50 years of age than in younger ones (8). It is therefore of great interest to study subjects over 50 years of age to define the prevalence and the phenotype of rhinitis.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in tree pollen allergy, many monosensitized subjects develop symptoms in old age (43,44). On the other hand, NAR appears to be more common in subjects over 50 years of age than in younger ones (8). It is therefore of great interest to study subjects over 50 years of age to define the prevalence and the phenotype of rhinitis.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…However, many patients have symptoms that mimick allergic rhinitis, with no definite causal factor and with a lack of demonstrated IgE-mediated allergy by skin prick tests and allergen-specific serum IgE (4). These patients have nonallergic rhinitis (NAR), sometimes ascribed to nonallergic, noninfectious rhinitis, and the prevalence in an adolescent/adult population with rhinitis is at least 25% (5)(6)(7)(8)(9). Although it is common, the prevalence in early childhood and school-age children is not well known.…”
Section: Magnitude Of the Problemmentioning
confidence: 99%
“…It was shown that the classic types of seasonal and perennial rhinitis cannot be used interchangeably with the new classification of IAR/PER, as they do not represent the same stratum of disease. Thus, ÔIARÕ and ÔPERÕ are not synonymous with ÔseasonalÕ and ÔperennialÕ (36,62,67,(81)(82)(83). In the original ARIA document, the number of consecutive days used to classify patients with PER was more than four per week (1).…”
Section: Intermittent (Iar) and Persistent Allergic Rhinitis (Per)mentioning
confidence: 99%
“…Epidemiological studies have revealed that the prevalence of AR has increased progressively in the moredeveloped countries, and currently affects up to 40% of the population worldwide (12)(13)(14)(15). Likewise, rising trend of AR has also been observed globally in the past decades; with a widely varying prevalence particularly in the developing nations, including in China (16).…”
Section: Introductionmentioning
confidence: 99%